Ultrasound in Obstetrics – More Safe? - Chołubek, Gustaw; Wiktor, Krzysztof; Robak-Chołubek, Dorota; Putowski, Lechosław; Wiktor, Henryk (Polish Journal of Public Health, 2012)
Nowadays, ultrasonography has become a basic diagnostic tool in prenatal medicine. In developed countries, most fetuses are exposed to ultrasound at least once throughout pregnancy. Safe use of ultrasound is imperative in fetal scanning. The paper presents bioeffects of ultrasound on living tissue and describes standards for safe use of ultrasound in obstetrics. Theoretical assumptions are related to the practical aspects of ultrasound examinations with the latest literature data on the safety of ultrasound in obstetrics.